NILAI TUKAR PENDAPATAN RUMAH TANGGA NELAYAN PENERIMA PROGRAM PEMBERDAYAAN EKONOMI MASYARAKAT PESISIR DI KABUPATEN TANJUNG JABUNG TIMUR - Asmaida Asmaida (Universitas Batanghari Jambi, 2015)
The East Tanjung Jabung regency area have a high potential of capture fisheries, with long beach approximately 191 km or 90,5 % from long beach Jambi, total area of capture fisheries about 97.631,31 ha with an average production of 21.094,775 tones/year and majority of population work as fishermen . The living conditions of fishermen still below the ideal level welfare of communities in general. In increase welfare of coastal communities y, government has done Coastal Community Economic Empowerment Program through provision of fishing vessels and fishing gears has been held since 2011, with the aim of improving welfare the coastal communities. This study aims to analyze household income fishermen, contributing to fishing, exchange rate household income fishermen, and welfare fishermen rate. The research was conducted in East Tanjung Jabung regency with survey method. In this case fishermen as a source of primary data, with technic collection of data is observation, interviews and charging questionnaire that have been patterned and structured accordance with the objectives of research. Agencies and literature as a source of secondary data. Technique of collection data is at random ( simple random sampling ) with total of sample 127 people (30%) of the total population (422 people). In analyze research data used method of descriptive qualitative and interperensi. Income (profits) were analyzed by the usage: π=TR–TC, contribution of income : Kt=(Pt/Prtn)x100%, exchange rate of fishermen NTP-RTN=Yrtn/Ertn, and the level of welfare fishermen INTP-RTN=(IYrtn/IErtn)x100 %. The results show after receiving the PEMP program the average number of per month: income of fishing business Rp.7.750.294. income of non fishing business Rp.440.157. Income the total households fishermen Rp.6.819.616, contribution of fishing business to total income households fishermen Rp.7.750.294 (92%) and Rp.440.157 (8%) from non fishing business. The exchange rate income the total households fishermen amounted to 3.08 and income of fishing business amounted to 6,03, this showed that households fishermen concerned have a welfare be enough to cover the primary his life and have the potential to consume a non-primary requirement or saving. The welfare of fishermen after receiving moderately prosperous PEMP program and the purchasing power of fishing communities has increased, it can be seen from the exchange rate index income the total households fishermen amounted to 134.51 and income of fishing business amounted to 136,22, where this number is above the price of the base year (the price base year = 100).Keywords: NTP-RTN, Income, Contributions, PEMP Program